Perfil dos eventos adversos registrados nos estudos de bioequivalência realizados na Unidade de Farmacologia Clínica no período de 2000 a 2003 - Guzzo, Giovanni Carvalho (2004)
The inexistence of medicines that act only in one target cell leads to a possible interaction at others cell structures which are not related to their therapeutic action, coming to the appearance of adverse drug reactions (ADR). The Pharmacovigillance System may lead to a better ADR analysis at a health or research institution, making itself essential for adverse events (AE) registering throughout clinical trials and more efficient investigation and notification afterwards. With the objective of evaluation of AE registered during bioequivalence trials, it was done a retrospective analysis of the voluntaries profiles from these trials in the period of 2000 to 2003. It was evaluated the frequency and the incidence of the events observed from the main pharmacological groups involved in the trials. For the two events more frequent from each pharmacological group, it was evaluated their causuality registered according to the present information found at the scientific literature. A total of 625 AE were analyzed with a mean value of 156 events per year, an incidence of 55,8% of AE per trial and a frequency of 13,89%. To make a standard causuality classification, it was proposed a specific classificatory model for bioequivalence trials. Therefore, the implementation of a standard method for AE causuality classification is essential for a better interpretation and safer notification of ADR.